Positive ion motion in cathode sheath of glow discharge in N₂O - Lisovskiy, V.A.; Artushenko, E.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2013)
It is established which of the Child-Langmuir collision law versions is most appropriate for describing the processes in the cathode sheath in the N₂O. At low pressure (up to 0.3 Torr) the Child-Langmuir law version relating to the constant ion mobility holds. At N₂O pressure values starting from 0.75 Torr and above, one have to employ the law version for which it is assumed that the ion mean free path within the cathode sheath is constant. In the intermediate pressure range (between 0.3 and 0.75 Torr) neither of the Child-Langmuir law versions gives a correct description of the cathode sheath of the glow discharge in the N₂O.